Analisis Data Well Logging Untuk Mengetahui Lapisan Akuifer Sumur Bor Di Kabupaten Hulu Sungai Selatan, Kalimantan Selatan - Al Rosyid, Ulil Abror; Siregar, Simon Sadok; Wahyono, Sri Cahyo (Universitas Lambung Mangkurat, 2024)
This research aims to analyze well logging data to determine the aquifer layer of drilled wells in Hulu Sungai Selatan Regency, South Kalimantan. This information is very important for sustainably developing groundwater resources in the region. This research uses well logging data collected from various sources, including resistivity, gamma rays, and spontaneous potential logs. These data are then analyzed using various techniques such as correlation analysis, log interpretation charts, and software to identify aquifer zones based on their characteristic log responses. The analysis succeeded in identifying potential aquifer layers in the wells studied. Aquifers are characterized by resistivity, gamma rays, and lithology. Based on the results of the analysis using WellCad data, four types of rock were obtained, namely: weathered rock (top soil), sand, clay, and sandy clay. Demonstrates the effectiveness of well logging data analysis in identifying and characterizing aquifer layers. Based on these results, it is known that the distribution of confined aquifers and unconfined aquifers has water-carrying properties. So overall it can be concluded that Hulu Sungai Selatan Regency has quite large deep groundwater potential because there are many layers of sand.KEYWORDS: Well logging; aquifer; groundwater; Hulu Sungai Selatan; South Kalimantan.